Textile omnidirectional antenna for wearable WiFi-7 applications using higher order modes - Noghanian, Sima (Frontiers in Antennas and Propagation, 2024)
In WiFi 7 (IEEE 802.11be), Multiple Input Multiple Output (MIMO) technology plays a crucial role in enhancing throughput. This combination enables numerous applications for wearable WiFi devices. For instance, WiFi can be utilized for tracking and fall detection purposes. Additionally, wearable devices used in gaming, vital signal monitoring, and tracking can benefit from the implementation of wearable MIMO antennas. Despite the demand for wearable WiFi antennas, specifically in the new 6 GHz band, a significant gap exists in the investigation of antennas that are completely made of textile, are low profile, and provide vertical polarization and omnidirectional patterns. Addressing this gap, in this paper, a wearable planar antenna is introduced, which is specifically designed to offer an omnidirectional pattern and linear polarization. To ensure its practicality and ease of use, the antenna utilizes lightweight and wearable textile material. The design details and performance of the proposed antenna are presented.